Challenges of nurses' performance in prenatal care of women deprived of their liberty (Research, Society and Development, 2022)
This article aims to analyze the prenatal care that is offered by the prison system to Brazilian women deprived of their liberty, they are in a vulnerable situation and the necessary consultations and follow-ups are not carried out during pregnancy, in the absence of assistance, many of them discover that they only carry an STI at the time of delivery, due to the lack of rapid tests that should be done in prenatal consultations. The structure is not suitable for postpartum women and newborns where there is a lack of rooming-in, since a large part of the prison population is male and the prison structure ends up being aimed at this public, there is no multidisciplinary team available for pregnant women to be holistically assisted. It is necessary to promote public policies of the penitentiary system regarding the health care of women and babies, and that they be put into practice in all Brazilian penitentiaries, thus aiming to promote integral action valuing the reeducated at this stage of her life.